Perbedaan Tingkat Depresi Pada Wanita Usia 45 - 60 Tahun Yang Belum Menopause Dan Yang Sudah Menopause Di Kartasura - Mariono, Iwan (2016)
Background: Estrogen is a stabilizer composition by nerve of the vegetative, so estrogen deficiency could predispose of the body organs. Estrogen influence the neurotransmitter system and the decline of the estrogen can be a deficiency of serotonin , norepinephrine and dopamine in the Central Nerves System , which affects the emergence of depression. In addition due to hormonal factors , geographical environment residence may also affect the occurrence of depression in women either premenopausal or menopausal Objective: To determine the depression difference level in women aged 45-60 Years not menopause and has menopause in District of Kartasura. Methods: This research is a label of observational study, with cross sectional approach. Received data is using of random sampling purposes with sample of 31 premenopausal women and 31 postmenopausal women. This research used analysis test that is unpaired t test. Results: There is a difference in degree of depression among women who yet already menopause and has menopause in District of Kartasura with value of p<0.01 That means highly statistically significant. Conclusion: There is significant between of premenopausal women and postmenopausal in District of Kartasura.